EXPERIMENTAL STUDY OF UREA GRANULATION - Irshad, U.; Sharif, M. N.; Rabbani, F.; Rauf, A.; Saleem, M. (The Nucleus, 2020)
Urea is a nitrogenous fertilizer available in two commercial forms, prills and granules, in Pakistan. Prills are more common in Pakistan, however, it has some problems associated with it. Those are moisture, biuret contents of urea prills, prill size, hardness of prills, caking of prills and urea dust emission. Due to these problems urea granulation is favoured over prilling. Urea granulation is studied on laboratory scale using pan granulator and effect of different parameters like binders (water and urea solution), quantity of binders, rpm of pan granulator, time of granulation and angle of inclination on granulation yield is studied. Water and urea solutions of different concentrations are used and results reveal that concentration of urea solution is proportional to rate of granulation. A threshold quantity of binder is required for optimum granulation yield. RPM of pan is inversely proportional to rate of granulation. Granulation yield is also proportional to time of granulation however it becomes critical at a certain point. Angle of inclination of pan has no significant effects on granulation yield.